[PP.16.12] THE PERSONALIZED NOCTURNAL BLOOD PRESSURE FALL IS NECESSARY TO DETERMINE THE ASSOCIATION BETWEEN VASCULAR DAMAGE AND BP DIPPING: A WARNING FOR CLINICAL OUTCOMES. (September 2017) - Nazzaro, P.; Schirosi, G.; De Benedittis, L.; Caradonna-Moscatelli, F.; Contini, M.; Aceto, G.; Papagni, A.M.; Federico, F.
Abstract : Objective: Many studies showed that a reduced nocturnal blood pressure (BP) percent fall (FALL) is associate to the vascular damage in hypertensives (HTN). Aim of the study was to recognize if the association was confirmed when the "real sleep time" was determined. Design and method: We studied 97 normotensives (ntn:125 ± 7/72 ± 10), 95 untreated hypertensives (htn), with lower (htnLIMT: 148 ± 13/88 ± 11) and 112 with higher (htnHIMT:149 ± 13/88 ± 11) carotid intima media thickness. ABPM, combined with simultaneous actigraphy, placed at the controlateral arm, let to determine the diurnal physical activity (>d3METs) time (min) and SBP FALL both as standard (FALLstd = 23.00–07.00) and personalized (FALLper = during "real awake/real sleep time") detected by muscular tone drop and sleep duration (SLEEP = min). Then, by videocapillaroscopy, the capillary density of the medial and distal phalanx of the 2nd, 3rd and 4th finger of the non-dominant hand at rest (CAP) and during venous congestion (CVC), as indices of structural and functional microvascular damage, were determined. Results: Patients showed similar age and metabolic characteristics but, in order of the standard or personalized sleeping time, different SLEEP (480 ± 00 vs 363 ± 98 *** ), FALL (11, 8 ± 7.8 vs 14.3 ± 7.7 *** ), vascular and BP traits (m ± s.d:. * :p < .05, ** :p < .01, *** :p < .001 vs NTN, ^:p < .05, ^^:p < .01, ^^^:p < .001 vs htnLIMT). Figure. No caption available. Pearson analyses, adjusted for age, physical activity, smoke and metabolic features, showed that IMT was associated to FALLstd −0.301 *** ) and FALLper (−0.156 * ) and, analogously, CVC was associated to FALLstd (−0.183 * ) but not to FALLper (−0.139). Conclusions: The results show that the reduced sleeping time, not considered through the standard 23.00–07.00 interval, including in contrast, awake hours, may induce an overestimation of the association between reduced nocturnal blood pressure fall and the macro- and micro-vascular damage in hypertensives.